Medieval Paradigms: Volume I
XXIV, 287 p.
Keywords: This collection of essays in two volumes explores patterns of medieval society and culture, spanning from the close of the late antique period to the beginnings of the Renaissance. In the first volume, the articles unravel the complexities of authority and community, and then turn to the multiple rubrics of behavior which bound and defined medieval societies. Volume 1 thus ends with a discussion of morality, from models of civic virtue (and vice) to Christian prescriptions and prohibitions.